Evidence of transmission of a Panton–Valentine leukocidin‐positive community‐acquired methicillin‐resistant Staphylococcus aureus clone: a family affair. (26th February 2013) - Cocchi, P.; Taccetti, G.; Montagnani, C.; Campana, S.; Galli, L.; Braggion, C.; de, M.; Lina, G.
Abstract Community‐acquired methicillin‐resistant Staphylococcus aureus (CA‐MRSA) may represent a serious public health problem, owing to the spread of toxin‐producing lineages. The presence of genes encoding for Panton–Valentine leukocidin (PVL) is an important virulence marker, as the clinical sequelae of PVL‐positive infections are often described as more severe than those of PVL‐negative S. aureus infections. To date, the presence of PVL has not appeared to be common in Italy; we describe the intrafamilial transmission of an epidemic PVL‐producing CA‐MRSA lineage, Southwest Pacific clone (SWP). Our data suggested that the strain circulated from the father, who was recurrently affected by a soft tissue infection, to the mother, who showed nasal colonization, and to their child, who was hospitalized with symptoms of necrotizing pneumonia. In this case, we found that a recurrent skin infection that is not normally taken into account may represent a serious threat if caused by a PVL‐producing strain. Our findings may have considerable implications for strategies for infection control and treatment of methicillin‐resistant S. aureus infections.